2021
DOI: 10.1002/jor.25155
|View full text |Cite
|
Sign up to set email alerts
|

Raman needle arthroscopy for in vivo molecular assessment of cartilage

Abstract: The development of treatments for osteoarthritis (OA) is burdened by the lack of standardized biomarkers of cartilage health that can be applied in clinical trials. We present a novel arthroscopic Raman probe that can "optically biopsy" cartilage and quantify key extracellular matrix (ECM) biomarkers for determining cartilage composition, structure, and material properties in health and disease. Technological and analytical innovations to optimize Raman analysis include (1) multivariate decomposition of cartil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…To enable molecular specific reconstruction, we employ multivariate regression of purified components. 29 3-D image reconstruction and rendering can finally be performed using inverse Radon transform - backprojection of the regression component abundances (Figure 1B). 30…”
Section: Resultsmentioning
confidence: 99%
“…To enable molecular specific reconstruction, we employ multivariate regression of purified components. 29 3-D image reconstruction and rendering can finally be performed using inverse Radon transform - backprojection of the regression component abundances (Figure 1B). 30…”
Section: Resultsmentioning
confidence: 99%
“…Kroupa et al [ 42 ] utilized a needle arthroscopic Raman probe for acquiring spectra, which were decomposed into composition-specific scores for GAGs, collagen, and water. In addition, polarized Raman spectra were collected to quantify collagen anisotropy in abraded cartilage samples.…”
Section: Discussionmentioning
confidence: 99%
“…32 To date, Raman needle arthroscopy has been developed and reported. 33 Kroupa et al 34 demonstrated Raman needle arthroscopy in both ex vivo and in vivo measurements for probing the cartilage surface of the knee joint. Our group has been developing a fiber-optic Raman spectroscopic system for endoscopic applications in animal and human optical biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, Raman needle arthroscopy has been developed and reported 33 . Kroupa et al 34 . demonstrated Raman needle arthroscopy in both ex vivo and in vivo measurements for probing the cartilage surface of the knee joint.…”
Section: Discussionmentioning
confidence: 99%